Retracing Alfred Russel Wallace's 1857 expedition to the Maros karsts of Sulawesi. (14th February 2019) - Brumm, Adam; Shagir, Kama Jaya; Ismail, Taufiq; Hakim, Budianto; Perston, Yinika; Newman, Kim; Macknight, Campbell
Abstract: Alfred Russel Wallace's forays in Southeast Asia led to his formulation of a theory that revolutionized our understanding of the history of life. Although Wallace was a prolific writer, his travel accounts are inconsistent with regards to details about his activities at given points in his journeys, especially in relation to the whereabouts of the many temporary abodes (e.g. huts) he used in the field. Hence, much of what Wallace did in the 'Malay Archipelago' remains unknown. In 1857, Wallace spent 2 months collecting in the limestone karsts of Maros in Sulawesi. Throughout this period, Wallace stayed on the estate of a local Dutch-Indische farmer, Jacob Mesman. Wallace vividly described the scenery and biodiversity of Maros, but his report of this expedition generally lacks detail. Here we use Wallace's written narratives, local histories and landscape surveys to identify the location of Mesman's estate where Wallace was based during his time in Maros. We also discuss our attempt to locate the site of the hut Wallace used as his collecting station. This is essential for a more complete understanding of Wallace's 1857 Sulawesi trip, an excursion that took place just a few months before he wrote his famous 'Ternate essay' in February 1858.